ILLEGAL CIRCULATION OF DRUGS USING THE INTERNET OR OTHER INFORMATION AND TELECOMMUNICATION NETWORKS - Musaev Djamaliddin Kamalovich (Journals Park Publishing, 2023)
Reveals topical problems in our days associated with drug trafficking using the telecommunications network of the Internet and various mobile applications that allow criminals to increase the turnover several times and at the same time remain out of sight of law enforcement agencies. Modern criminal trends show that the global Internet is increasingly being used as a way to distribute drugs. The article deals with typical investigative situations in cases of crimes related to drug trafficking committed via the global Internet. The features of drug trafficking committed through the global Internet are analyzed. Recommendations are given to improve the efficiency of investigating crimes related to drug trafficking through the global Internet.
Keywords: investigation of crimes, UN recommendations INCB, drug trafficking, global Internet networks, drug trafficking, drug business, law enforcement agencies, Internet, telecommunications networks, contactless sale of drugs, cyber patrol.